Neurodevelopment in Down syndrome: Concordance in humans and models - Klein, Jenny A.; Haydar, Tarik F. (Frontiers in Cellular Neuroscience, 2022)
Great strides have been made over the past 30 years in understanding the neurodevelopmental changes underlying the intellectual disability (ID) in Down syndrome (DS). Detailed studies of human tissue coupled with findings from rodent and induced pluripotent stem cells (iPSCs) model systems have uncovered the changes in neurogenesis, synaptic connectivity, and myelination that drive the anatomical and physiological changes resulting in the disability. However, there remain significant conflicting data between human studies and the models. To fully understand the development of ID in DS, these inconsistencies need to be reconciled. Here, we review the well documented neurodevelopmental phenotypes found in individuals with DS and examine the degree to which widely used models recapitulate these phenotypes. Resolving these areas of discord will further research on the molecular underpinnings and identify potential treatments to improve the independence and quality of life of people with DS.